2011
DOI: 10.1073/pnas.1019273108
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of imprinted gene expression in Arabidopsis endosperm

Abstract: Imprinted genes are expressed primarily or exclusively from either the maternal or paternal allele, a phenomenon that occurs in flowering plants and mammals. Flowering plant imprinted gene expression has been described primarily in endosperm, a terminal nutritive tissue consumed by the embryo during seed development or after germination. Imprinted expression in Arabidopsis thaliana endosperm is orchestrated by differences in cytosine DNA methylation between the paternal and maternal gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
551
1
5

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 314 publications
(602 citation statements)
references
References 51 publications
40
551
1
5
Order By: Relevance
“…For some genes expression of the maternal allele was also upregulated. This and another study concluded that PRC2 can regulate maternal and paternal alleles of MEGs and maternal alleles of PEGs [5] [6]. In endosperm, paternal alleles of PEGs might be protected from PRC2 repression because of DNA methylation continuously present at those loci [25].…”
Section: Polycomb Groupmentioning
confidence: 82%
See 4 more Smart Citations
“…For some genes expression of the maternal allele was also upregulated. This and another study concluded that PRC2 can regulate maternal and paternal alleles of MEGs and maternal alleles of PEGs [5] [6]. In endosperm, paternal alleles of PEGs might be protected from PRC2 repression because of DNA methylation continuously present at those loci [25].…”
Section: Polycomb Groupmentioning
confidence: 82%
“…Deep sequencing of mRNA libraries derived from reciprocal intraspecific crosses of Arabidopsis thaliana, rice, and maize has proven to be an effective strategy to identify genes that are preferentially expressed from one parental allele during seed development [4][5][6][7][8][9]. These studies have confirmed that imprinting is mostly endosperm-specific and have significantly expanded the number of imprinted genes to between about 50-200 in each species.…”
Section: Genomic Studies Of Imprintingmentioning
confidence: 99%
See 3 more Smart Citations